Inequity in health care utilization for common childhood illnesses in India: measurement and decomposition analysis using the India demographic and health survey 2015-16 - Tulasi Malini Maharatha; Umakant Dash (BMC, 2021)
Abstract Background Though child mortality has dropped remarkably, it is considerably high in South Asia. Across the globe, 5.2 million children under 5 years of age died in 2019, and India accounts for a significant portion of these deaths. Common childhood illnesses are the leading cause of these deaths. Seeking care from formal providers can reduce these avoidable deaths. Inequity is a crucial blockage in optimum utilization of medical treatment for children. Hence, the present study analyzes the inequalities and horizontal inequities in utilizing the medical treatment for diarrhea, fever, acute respiratory infection (ARI), and any of these common childhood illnesses in India and across the Indian states. The study also attempts to locate significant contributors to these inequalities. Methods The study used 0 to 59 months children's data sourced from the Demographic and Health Survey, India (2015-16). Concentration Index (CI) and Erreygers Corrected Concentration Index (EI) were used to measure the inequalities. The Horizontal Inequity Index (HII) was deployed to estimate inequity. The decomposition method introduced by Erreygers was applied to determine the significant contributors of inequalities. Results The EI in medical treatment-seeking for common childhood illnesses was 0.16, while the HII was 0.15. The highest inequality was perceived in the utilization of medical treatment for ARI (0.17). The primary contributing factors of these inequalities were continuum of maternal care (18.7%), media exposure (12%), affordability (9.3%), place of residence (9.1%), mother's education (8.5%), and state groups (8.8%). The North-Eastern states showed the highest level of inequality across the Indian states. Conclusion The study reveals that the horizontal inequity in medical treatment utilization for children in India is pro-rich. The findings of the study suggest that attuning the efforts of existing maternal and child health programs into one seamless chain of care can bring the inequalities down and improve the utilization of child health care services. The spread of health education through different media sources, reaching out to rural and remote places with adequate health personnel, and easing out the financial hardship in accessing medical treatment could be the cornerstone in accelerating the utilization level amongst the impoverished children.